Surface morphology of Diplodon expansus (Kuster, 1856; Mollusca, Bivalvia, Hyriidae) gill filaments after exposure to environmentally relevant concentrations of atrazine herbicide - Nogarol, Larissa Rosa [UNESP]; Brossi-Garcia, Ana Luiza [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Wiley-Blackwell, 2012)
Brazilian endemic species Diplodon expansus (Kuster, 1856) is found in freshwater bodies in the country's southeast, in large anthropogenic influence regions especially with an extensive agriculture emphasis. One of the main pesticides used in the species occurrence region is the atrazine herbicide, which has a great contamination potential in the aquatic environment. Therefore, several studies into its toxicity in aquatic systems have been developed. However, the tested concentrations are usually very high and rarely found in the environment and the short-term exposure responses in other aquatic organisms such as native bivalves are still scarce. Thus, this study sought to consider the potential effects of environmentally realistic concentrations of atrazine herbicide on the surface morphology of gill filaments of the bivalve D. expansus under laboratory-controlled conditions after short-term exposure. None of the animals died before the end of the experiment. The main alterations were observed on the frontal surface of filaments, which include mucus accumulation, cilia loss, and disruption. Mucus increased secretion and accumulation in the frontal filaments region preceded as a protective mechanism. Cilia loss and disruption on the frontal surface of the gill filament indicated that ciliated frontal cells were more sensitive to atrazine exposure and these alterations may cause gills functional damages, compromising the uptake of food particles and respiration. Therefore, higher sublethal concentrations of atrazine may compromise the survival and consequently the population of D. expansus in agriculture areas after a longer period of continuous exposure. Microsc. Res. Tech. 75:807813, 2012. (C) 2011 Wiley Periodicals, Inc.
Keywords: mussel; pesticide; SEM; ctenidia